Geochemical signature of the Pomarinho enclave swarm (Ossa-Morena Zone, Portugal) - Moita, P. (2012)
The enclave swarm of Pomarinho is located in the SW edge of Évora granitoid (Carvalhosa, 1983), in the SW sector of the Ossa-Morena Zone (Iberian Variscides). The Granialpa quarry constitutes a privileged exposure of that swarm and, therefore, it was used to collect samples for AMS, petrographic and geochemical studies. The dominant rock in the quarry is a medium-grained granodiorite, composed of plagioclase, quartz, alkali feldspar and biotite. This granodiorite displays a weak N-S planar anisotropy, de-fined by the arrangement of ferromagnesian minerals (mainly biotite). Dark-colored and fine-grained enclaves, that do not exceed 1% volume of the host rock, can be observed scattered throughout the quarry. However, in the NW part of the quarry, there is a cluster of enclaves which, locally, corre-spond to 40-50% of the volume of the host rock. These enclaves exhibit a significant variability in modal composition and texture; therefore, they constitute a heterogeneous swarm, according to Tobish et al. (1997). The enclaves correspond to tonalites and granodiorites, with either equi-granular or porphyritic textures. Their modal compositions comprise essentially the same minerals found in the host granitoid; the major differences are the higher abundances of biotite and plagioclase and the occurrence of small amounts of hornblende, in the enclaves. AMS measurements on both the enclaves and the host rock are very consistent and show that magnetic lineations (K1) have a N-S trend and a plunge of 36º to the South (Moita et al., 2010). Geochemically, the host granodiorite is very homogeneous considering most of the major elements. It is slightly peraluminous (A/CNK~1.03), corresponding to an I-type granite (White & Chapell, 1977). Regarding trace elements, this granodiorite exhibits negative Nb-Ta anomalies [(Th/Nb)N: 8.59-12.08; (La/Ta)N: 1.73-2.18], slightly LREE-enriched patterns [(La/Lu)N: 12.08-16.43] and negative Eu anomalies (EuN/EuN*: 0.73-0.81). The enclaves may be divided into two groups. The first comprises tonalites with SiO2 from 63% to 65%, MgO from 2.2% to 2.4%, Fe2O3t from 5.1% to 5.8%, CaO from 4.1% to 4.8% and TiO2 from 0.7% to 0.9%. Their A/CNK ratios lie in the range 0.98-1.03 and, therefore, they may be considered metaluminous to weakly peraluminous. The trace element geochemistry, similarly to the host, is characterized by the negative Nb-Ta anomalies [(Th/Nb)N: 4.45-6.86; (La/Ta)N: 2.02-2.65] and the slight enrichment in LREE [(La/Lu)N:9.12-11.38]. The second enclave group, with granodioritic compositions, is always slightly peraluminous (A/CNK ~ 1.05), and has higher SiO2 and lower MgO, Fe2O3, CaO and TiO2 values compared to the tonalitic enclaves. Compared to the host rock, the granodioritic enclaves have higher CaO and Na2O and lower K2O contents. The multi-element patterns of the second enclave group also show negative Nb-Ta anomalies [(Th/Nb)N: 9.55 and 10.88; (La/Ta)N: 1.35 and 1,58] and a small LREE enrichment [(La/Lu)N: 9.48 and 12.86]. This preliminary geochemical information suggests that the enclaves and the host rock are probably derived of co-genetic magmas. In such a picture, the tonalitic enclaves and the host granodiorite should represent different degrees of fractionation from the same parental magmas. The granodioritic enclaves, on the other hand, may represent a strong mechanical interpenetra-tion, but chemically incomplete, of the host granodiorite and the less evolved tonalite. Other da-ta, such as isotope geochemistry (in progress) and AMS information, are expected to bring new light to the discussion on the Pomarinho enclave swarm genesis and evolution.